Factors Affecting Depression And Suicidal Tendency Among The Students For The Educational Process: A Study On Sylhet, Bangladesh. - Muhammad Al Amin; Md Mehdi Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The study wants to assess the factors that affect depression and suicidal tendencies among the students of Shahjalal University of science and technology and MC College, Sylhet. For collecting data and questionnaire method was followed. The researcher selected 50 samples from both of these institutions. In this study, a mixed research approach has been followed. The study disclosed that among the respondents, 90% had an idea about depression, and 90% got depression once in their lifetime. They suffered from major depressive disorder, bipolar disorder, and premenstrual dysphoric disorder, etc. and suffered from bipolar disorder. Depression has an adverse effect on student's academic life. Besides, 72% said that they need more consciousness about their depression. The study also revealed that 8% are also addicted to different drugs and alcohol. The study further revealed that 64% thought that the severity of depression could lead someone to commit suicide and 28% said that they thought about suicide during their depression period. The study also recommended that one should pass their time doing activities that can help reduce stress. In their leisure time, they can gossip with their friends, and sharing their feeling with good friends can be another solution to anxiety. The study further added that if they failed, they might commit suicide at a severe level of their depression.